Effectivity of sea grape extract (Caulerpa Sp.) against wound cure on the angle of wistar white rats (Rattus norvegicus) lips induced by Staphylococcus aureus and Candida albicans: Efektivitas ekstrak anggur laut (Caulerpa Sp.) terhadap penyembuhan luka pada sudut bibir tikus putih wistar (Rattus norvegicus) yang diinduksi Staphylococcus aureus dan Candida albicans - Sumintarti; Putri Mujahidah; Ali Yusran; Harlina; Haswamati Hasan (Makassar Dental Journal PDGI Makassar, 2022)
Introduction: Apart from fish, other marine products that can be processed are seaweed. Sea grape (Caulerpa Sp.) is one of the seaweeds, which contains active ingredients, namely flavonoid, saponin, carotenoid, phenol, alkaloid and tannin which are use-ful as antioxidant, antibacterial, antidiabetic and cytotoxin, antinociceptive and anti-inflammatory. Objective: To determine the effect of sea grape extract towards wound healing on the corners of the lips of white wistar rats (Rattus norvegicus) induced by S.aureus and C.albicans, and to compare them with the antimicrobial gentamicin and the antifungal miconazole. Methods: Pure experimental research with posttest only control group design; the wound of 24 male wistar white rats divided into: group 1 in-duced by S.aureus and then given sea grape extract, group 2 induced by C.albicans then smeared with sea grape extract, group 3 induced by S.aureus then given gentamicin, and group 4 was induced by C.albicans and then given miconazole. The length of the wound was periodically measured as an indicator of the healing process. Data were analyzed using SPSS version 22.0. Re-sults: The effect on each group were tested using Friedman, showed significant in each group (p = 0.001). Different test with Mann Whitney group 1 and group 3 (antibacterial control) showed significantly different results on testing days 1-5; group 2 and group 4 (antifungal control) also showed significantly different results on days 1-4; groups 1 and 2 showed insignificant results. Conclusion: Sea grape extract had a significant effect on wound healing in the lip corners of male wistar rats induced by S.aureus and C.albicans. Sea grape extract had the same effect with positive antibacterial and antifungal control.